The local aggregate effects of minimum wage increases - Daniel Cooper; Maria José Luengo-Prado; Jonathan A. Parker (Federal Reserve Bank of Boston, 2017)
This paper examines the effect of minimum wage changes on local aggregate inflation and consumption growth. The paper utilizes variation in state-level minimum wages across locations and finds that minimum wage increases have a relatively modest effect on both city-level inflation and spending growth over the years following the change. The most noticeable effects are for food consumed at home and away from home - industries that typically employ a large share of low-wage and minimum-wage workers. Interestingly, consumers adjust their real food consumption when minimum wages rise, suggesting that some workers benefit from minimum wage changes.
Keywords: E21; E31; E64; 330; minimum wage increases; prices; consumption; local aggregate effects; Mindestlohn; Wirkungsanalyse; USA